2018
DOI: 10.1051/matecconf/201825003006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Fracture Energy of Foam Concrete at Different Notch Depth

Abstract: Foamed concrete is lightweight concrete formulated from a mixture of concrete mortar and established foam. Generally foamed concrete is known for its low engineering properties. Many researchers had conducted studies and more focused on the physical and mechanical properties of foamed concrete without taking into account the behavior on its fracture energy. Therefore, this study was carried out to investigate the effect of notch-to-depth ratio on fracture energy of foam concrete using three point bending testm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Regarding the comparison of the models, those of Hillerborg and Bazant showed an increase of G F with the density of the material, and very similar results among them, for FCC and cement mortar with self weight up to 2 000 kg/m 3 . In addition, Zamri et al [96] evaluated the fracture energy of FC beams with different notch-todepth ratios, and comparing the values obtained with the Hillerborg model, the CEB-FIB model, and with that of Bazant. They observed that G F decreases with increasing the ratio of the notch height to the beam height, and that the Hillerbog model is the most suitable.…”
mentioning
confidence: 99%
“…Regarding the comparison of the models, those of Hillerborg and Bazant showed an increase of G F with the density of the material, and very similar results among them, for FCC and cement mortar with self weight up to 2 000 kg/m 3 . In addition, Zamri et al [96] evaluated the fracture energy of FC beams with different notch-todepth ratios, and comparing the values obtained with the Hillerborg model, the CEB-FIB model, and with that of Bazant. They observed that G F decreases with increasing the ratio of the notch height to the beam height, and that the Hillerbog model is the most suitable.…”
mentioning
confidence: 99%